الثقة التنظيمية كمتغير وسيط في العلاقة بين إدارة المعرفة وتحسين أداء هيئة التدريس لدى أساتذة كلية العلوم الإقتصادية والتجارية وعلوم التسيير-جامعة الأغواط - جميعة فادية ملاك; بن برطال عبد القادر (جامعة عمار ثليجي الاغواط, 2022)
This study aimed to measure and analyze the relationship and impact between knowledge management and improving the performance of the teaching staff among the professors of the Faculty of Economics, Commercial and Management Sciences, Laghouat University, Algeria. storage and application of knowledge), and the dependent variable, which is improving the performance of the faculty, in addition to an intermediate variable represented in organizational confidence. Through this study, we found a statistically significant effect of knowledge management on improving the performance of the teaching staff among the professors of the Faculty of Economics, Commercial and Management Sciences at the University of Laghouat, Algeria, and that 64.50% of this effect was indirectly through organizational confidence on the study variables. The study also showed that there are no statistically significant differences in the effect of knowledge management on improving the performance of the faculty in the presence of the mediating variable (organizational confidence) at the Faculty of Economic, Commercial and Management Sciences - University of Laghouat - in the presence of personal and functional data (gender, age, years of service, academic degree (At the level of significance α = 0.05.